2019
DOI: 10.3390/cells8090980
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin-Enhanced Autophagy Attenuates Early Brain Injury via FAK–ERK Pathway and Improves Long-Term Outcome after Subarachnoid Hemorrhage in Rats

Abstract: Osteopontin (OPN) enhances autophagy, reduces apoptosis, and attenuates early brain injury (EBI) after a subarachnoid hemorrhage (SAH). A total of 87 Sprague–Dawley rats were subjected to sham or SAH operations to further investigate the signaling pathway involved in osteopontin-enhanced autophagy during EBI, and the potential effect of recombinant OPN (rOPN) administration to improve long-term outcomes after SAH. Rats were randomly divided into five groups: Sham, SAH + Vehicle (PBS, phosphate-buffered saline)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…47 Accumulating evidence has demonstrated that OPN plays a significant role in neurodegenerative diseases such as Alzheimer's disease, Parkinson's disease and multiple sclerosis, 26,27,48 as well as acute brain injury including TBI, stroke, and hypoxia-ischaemia brain injury. [49][50][51][52] Different acute brain injury models share many common features and processes within the pathophysiology. To date, most studies suggest a neuroprotective role of OPN in these neurological diseases.…”
Section: The Role S Of Os Teop Ontin In Acute B R Ain Inj Urie S Anmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Accumulating evidence has demonstrated that OPN plays a significant role in neurodegenerative diseases such as Alzheimer's disease, Parkinson's disease and multiple sclerosis, 26,27,48 as well as acute brain injury including TBI, stroke, and hypoxia-ischaemia brain injury. [49][50][51][52] Different acute brain injury models share many common features and processes within the pathophysiology. To date, most studies suggest a neuroprotective role of OPN in these neurological diseases.…”
Section: The Role S Of Os Teop Ontin In Acute B R Ain Inj Urie S Anmentioning
confidence: 99%
“…116,117 Emerging studies suggest that OPN enhances autophagy and reduces apoptosis after experimental SAH through FAK signalling, resulting in the attenuation of early brain injury and improvement of long-term outcome. 51…”
Section: Opn and Apoptosismentioning
confidence: 99%
“…Abnormal autophagy facilitates caspase-dependent neuronal apoptosis (Chung et al 2018). Enhancement of autophagy ameliorates neuronal apoptosis and subsequent neurological deficits after SAH in rats (Shao et al 2016;Sun et al 2019). By contrast, mitophagy-induced oxidative stress promotes neuronal death after SAH (Zhang et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The left hemispheres were removed from brains and fixed in 4% paraformaldehyde for 24 hours and then incubated in 30% sucrose for 48 hours. Hippocampal coronal sections 16 μ m thick were taken using a Thermo NH50 cryostat, and 0.5% crystal violet was used for Nissl staining as in the previous study [ 30 ]. The morphological changes of neurons in the different positions of the hippocampus were observed under a light microscope at 200x magnification by two independent observers.…”
Section: Methodsmentioning
confidence: 99%